Penambahan Kader TB Guna Mencegah Penularan Penyait TBC Di Desa Walidono Kecamatan Prajekan Kabupaten Bondowoso - Andry Sulistyanto; Anggun Nilamsani; Irawati Fatikasari (Jurnal Informasi Pengabdian Masyarakat, 2023)
Cadres are a group of people who are fostered by a management agency in an organization that functions to assist the organization's tasks. Activating TB cadres is an alternative in efforts to prevent and control Tuberculosis (TB) sufferers in Walidono Village, Prajekan District, Bondowoso Regency. The activation of TB cadres will begin with mentoring activities related to procedures that will be carried out in the future in efforts to prevent and control tuberculosis (TB) sufferers. The benefit of reactivating TB cadres is the creation of efforts to help cure and reduce Tuberculosis (TB) sufferers. This program is an alternative effort that can be carried out in a sustainable manner to help people with Tuberculosis (TB).